Struggling for survival in the village after the disturbance of tobaccoland: Tracing new rurality behind the footprints of tobacco farmers - Kavak, Sinem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This thesis traces the impacts of neoliberalization of tobacco production and market on the rural households in tobacco producing villages in addition to the attempts of survival and patterns of restructuring of tobacco livelihoods. In search for answers, a field research was performed in the villages of Adıyaman, Soma (Manisa) and Fethiye (Mugla) which included in-dept interviews with the producers, local officials and representatives of subcontracting firms. Moreover, the qualitative data were combined with macro statistics on demography, population, production and socioeconomic indicators. The findings are placed within the broader historical and theoretical framework in order to present a grounded, coherent picture of the phenomenon under scrutiny. The thesis reveals two major patterns. Primarily, agricultural production does not yield sufficient income for the survival and recreation of the peasant household in arid and semi-arid tobacco villages which necessitates integration of off-farm income sources to the household budget. The result is either permanent migration- which is also troublesome for the peasants- or income diversification through pluriactivity, off-farm diversification, seasonal migration, and circular migration. Thus a constant movement of peasants between rural and urban areas takes place indicating a new type of rurality by undermining the conceptual relevance of dualistic terms such as “rural” and “urban”, “worker” and peasant” Secondly the thesis reveals that inequality and poverty increase in the rural areas due to diversified diversification sites of the peasants. In villages with job opportunities in the near surroundings preservation and recreation of rural life is more likely than in the villages with less income opportunities in the near surroundings. Moreover, worse-off farmers diversify mostly in unfavorable and informal markets whereas better-off farmers diversify in better markets with opportunities to move other sectors. This phenomenon leads to the disruption of relatively egalitarian social structure in rural Turkey. In addition, the thesis elaborates on indebtedness, dispossession and deprivation of the poor peasantry. Furthermore, the thesis argues that tobacco production will be transferred to poorer households with less income diversification opportunities and with exploitable labor reserve that is because high vulnerability levels of such households situate them to a weak position before profit seeking subcontracting firms and transnational tobacco industry enabling the firms dictate their terms along their interests over the weak peasantry with no alternative.
Keywords: Agriculture -- Economic aspects.; Agriculture and state -- Turkey.; Tobacco industry -- Turkey.